The distribution of BRAF gene fusions in solid tumors and response to targeted therapy. Issue 4 (8th September 2015) - Ross, Jeffrey S.; Wang, Kai; Chmielecki, Juliann; Gay, Laurie; Johnson, Adrienne; Chudnovsky, Jacob; Yelensky, Roman; Lipson, Doron; Ali, Siraj M; Elvin, Julia A.; Vergilio, Jo‐Anne; Roels, Steven; et al.
Abstract : Although the BRAF V600E base substitution is an approved target for the BRAF inhibitors in melanoma, BRAF gene fusions have not been investigated as anticancer drug targets. In our study, a wide variety of tumors underwent comprehensive genomic profiling for hundreds of known cancer genes using the FoundationOne™ or FoundationOne Heme™ comprehensive genomic profiling assays. BRA F fusions involving the intact in‐frame BRAF kinase domain were observed in 55 (0.3%) of 20, 573 tumors, across 12 distinct tumor types, including 20 novel BRAF fusions. These comprised 29 unique 5′ fusion partners, of which 31% (9) were known and 69% (20) were novel. BRAF fusions included 3% (14/531) of melanomas; 2% (15/701) of gliomas; 1.0% (3/294) of thyroid cancers; 0.3% (3/1, 062) pancreatic carcinomas; 0.2% (8/4, 013) nonsmall‐cell lung cancers and 0.2% (4/2, 154) of colorectal cancers, and were enriched in pilocytic (30%) vs . nonpilocytic gliomas (1%; p  < 0.0001), Spitzoid (75%) vs . nonSpitzoid melanomas (1%; p  = 0.0001), acinar (67%) vs . nonacinar pancreatic cancers (<1%; p  < 0.0001) and papillary (3%) vs . nonpapillary thyroid cancers (0%; p  < 0.03). Clinical responses to trametinib and sorafenib are presented. In conclusion, BRAF fusions are rare driver alterations in a wide variety of malignant neoplasms, but enriched in Spitzoid melanoma, pilocytic astrocytomas, pancreatic acinar and papillary thyroid cancers. Abstract : What's new? New results may help target a rare genetic alteration that promotes cancer. Activation of the BRAF gene is already known to spur tumor growth, and usually that activation results from a single amino acid substitution. BRAF‐inhibiting treatments, then, target that mutation. However, in some cases, BRAF gets revved up by a gene fusion. In our study, the authors tested 20, 000 tumors and identified 55 BRAF gene fusions in 12 different tumor types. They found the gene fusions occurred more frequently in certain histologic subtypes, information which will help guide treatment strategies for patients with these tumor subtypes.